1984
DOI: 10.1136/gut.25.6.682
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomised trial of early cytotoxic therapy for recurrent colorectal carcinoma detected by serum CEA.

Abstract: SUMMARY Of 663 patients treated with radical surgery for colorectal cancer, 52 showed a progressive rise in serum carcinoembryonic antigen (CEA) with no other evidence of recurrent disease and were randomised in a prospective study of chemotherapy. Twenty six patients in the treatment group received 5FU and methyl CCNU from the time of randomisation and the remaining 26 controls were given further therapy only if there were clinical indications. All patients were followed for five years or until their death an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

1984
1984
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Tumour antigen levels have been used for many years in the clinical management of cancer (Goldenberg et al, 1981). They have proved of value in detecting recurrent disease (NIH Consensus Statement, 1981;Hida et al, 1996), monitoring the effects of chemotherapy and predicting prolonged survival (Hine and Dykes, 1984;AllenMersh et al, 1987;Ward et al, 1993). A combined analysis of marimastat clinical trials, in patients with carcinoma of the pancreas, ovary, colon and prostate, has demonstrated a dose-dependent reduction in the rate of rise of cancer antigens (Nemunaitis et al, 1998).…”
mentioning
confidence: 99%
“…Tumour antigen levels have been used for many years in the clinical management of cancer (Goldenberg et al, 1981). They have proved of value in detecting recurrent disease (NIH Consensus Statement, 1981;Hida et al, 1996), monitoring the effects of chemotherapy and predicting prolonged survival (Hine and Dykes, 1984;AllenMersh et al, 1987;Ward et al, 1993). A combined analysis of marimastat clinical trials, in patients with carcinoma of the pancreas, ovary, colon and prostate, has demonstrated a dose-dependent reduction in the rate of rise of cancer antigens (Nemunaitis et al, 1998).…”
mentioning
confidence: 99%
“…In advanced disease a clinical response rate to chemotherapy of over 40% has been reported (Moertel et al, 1975) although this has not been matched by an improvement in survival of treated patients (Buroker et al, 1978). In a study from our unit when cytotoxic therapy was given at the earliest evidence of recurrence, as indicated by a rise in CEA, a similar picture emerged with no overall benefit to treated patients in terms of survival (Hine & Dykes, 1984). However, a subgroup of patients who showed a significant fall in CEA seemed to derive clinical benefit from early therapy (Hine & Dykes, 1984).…”
Section: Resultsmentioning
confidence: 51%
“…Patients in whom routine screening showed a CEA concentration of > 20 ng ml-1 were recalled to clinic within 2 (Hine & Dykes, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…They had a total of 614 patients comparing chemotherapy to an initial observation arm in patients with metastatic colorectal cancer (Hine and Dykes, 1984;Nordic Gastrointestinal Tumour Adjuvant Therapy Group (NGTATG), 1992;Rougier et al, 1992;Scheithauer et al, 1993;Allen-Mersh et al, 1994;Hafstrom et al, 1994;Glimelius et al, 1995). These are listed in Table 1, along with a brief description of treatment schedules.…”
Section: Trials Selectedmentioning
confidence: 99%
“…A leading oncology text only references one study on this topic (Hine and Dykes, 1984;Cohen et al, 1997). This results in uncertainty for both patient and physician contemplating systemic therapy.…”
mentioning
confidence: 99%